2012
DOI: 10.1530/eje-11-0866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ethnicity on gestational diabetes identified with the WHO and the modified International Association of Diabetes and Pregnancy Study Groups criteria: a population-based cohort study

Abstract: ObjectiveThe International Association of Diabetes and Pregnancy Study Groups (IADPSG) recently proposed new criteria for diagnosing gestational diabetes mellitus (GDM). We compared prevalence rates, risk factors, and the effect of ethnicity using the World Health Organization (WHO) and modified IADPSG criteria.MethodsThis was a population-based cohort study of 823 (74% of eligible) healthy pregnant women, of whom 59% were from ethnic minorities. Universal screening was performed at 28±2 weeks of gestation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 32 publications
8
152
3
Order By: Relevance
“…A standard 75 g oral glucose tolerance test (OGTT) was performed at 28 weeks of gestation with fasting and 2-h plasma glucose analyzed on-site in venous EDTA blood samples (HemoCue, Angelholm, Sweden) (4). GDM was defined by the WHO 2013 criteria (23) (fasting glucose R5.1 mmol/l or 2-h glucose R8.5 mmol/l) and 1-h glucose was not available (4).…”
Section: Metabolic Variables and Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard 75 g oral glucose tolerance test (OGTT) was performed at 28 weeks of gestation with fasting and 2-h plasma glucose analyzed on-site in venous EDTA blood samples (HemoCue, Angelholm, Sweden) (4). GDM was defined by the WHO 2013 criteria (23) (fasting glucose R5.1 mmol/l or 2-h glucose R8.5 mmol/l) and 1-h glucose was not available (4).…”
Section: Metabolic Variables and Gdmmentioning
confidence: 99%
“…South Asian migrants to Europe have a high prevalence of type 2 diabetes (3) and gestational diabetes (GDM) (4). GDM is defined as first recognition of hyperglycemia during pregnancy (5).…”
Section: Introductionmentioning
confidence: 99%
“…The Regional Ethics committee and The Norwegian Data Inspectorate approved the study protocol. The methods are described in detail elsewhere (9,15). Women were eligible if they: i) lived in the districts; ii) planned to give birth at one of two study hospitals; iii) were at !20 weeks of gestation at visit 1 (V1); iv) could communicate in Norwegian, Arabic, English, Sorani, Somali, Tamil, Turkish, Urdu or Vietnamese; and v) were able to give written consent to participate.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…We recently reported that the prevalence of GDM with both the WHO and the modified IADPSG criteria was high for Western European and immigrant women living in Oslo (9). GDM is increasing in line with the diabetes type 2 prevalence worldwide (12,13).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation